Performance improvement of shunt active power filter based on indirect control with a new robust phase-locked loop - A. Chemidi; M. C. Benhabib; M. A. Bourouis (Electrical engineering & Electromechanics, 2022)
Introduction. Since the development of the first active power filter (APF) in 1976, many efforts have been focused on improving the performances of the APF control as the number of different nonlinear loads has continued to increase. These nonlinear loads have led to the generation of different types of current harmonics, which requires more advanced controls, including robustness, to get an admissible total harmonic distortion (THD) in the power system. Purpose. The purpose of this paper is to develop a robust phase-locked loop (PLL) based on particle swarm optimization-reference signal tracking (PSO-RST) controller for a three phase three wires shunt active power filter control. Methodology. A robust PLL based on PSO-RST controller insert into the indirect d-q control of a shunt active power filter was developed. Results. Simulation results performed under the MATLAB/SimPowerSystem environment show a higher filtering quality and a better robustness compared to the classical d-q controls. Originality. Conventional PLLs have difficulty determining the phase angle of the utility voltage sources when grid voltage is distorted. If this phase angle is incorrectly determined, this leads to a malfunction of the complete control of the active power filters. This implies a bad compensation of the current harmonics generated by the nonlinear loads. To solve this problem we propose a robust and simple PLL based on PSO-RST controller to eliminate the influence of the voltage harmonics. Practical value. The proposed solution can be used to improve the functioning of the shunt active power filter and to reduce the amount of memory implementation.